Tari Sufi dan Penguatan Pemahaman Keagamaan Moderat Kaum Muda Muslim (Studi Kasus Tari Sufi Karanganyar, Jawa Tengah) - Ayu Kristina (Lembaga penelitian dan pengabdian kepada Masyarakat, 2019)
Young Muslims as a driver of national change have an important role in introducing Islam that is friendly and open to the modern world. One of them is religious expression through Sufi dance developed by Jalaluddin Rumi. This study was conducted to find out how adolescents interpret Islam through Sufi dances and how Sufi dances that are followed can contribute to adolescents in daily life, especially in shaping attitudes and practices of moderate and tolerant religiosity. With a descriptive qualitative approach, through in-depth interviews from (8) informants who were determined based on purposive sampling the results of the study showed that Islam was interpreted as a pleasure, discipline, politeness that was not only illustrated through human relations with God but also humans and humans and other creatures around it. In social life a Sufi dancer must implement the noble character that is gained when studying Sufi dance. For example must be polite, and hap ashor (humble), patient, sincere, have peace of mind, educated, and able to control themselves.